Uji Tipe dan Ketinggian Perangkap untuk Mengendalikan Penggerek Buah Kopi Hypothenemus hampei Ferr. (Coleoptera : Scolytidae) di Desa Pegagan Julu II Kecamatan Sumbul Kabupaten Dairi - Winda Nuraini Situmorang Situmorang; Marheni; Ameilia Zuliyanti Siregar (Jurnal Pertanian Tropik, 2018)
Coffeeberry borer (Hypothenemus hampei) is one of the dominant pests that are difficult to control. This research was conducted to determine the effectiveness type and height of trap to control coffee berry borer in Sumbul, Dairi. The method used Factorial Randomized Block Design (RBD) which consisted of 2 treatments factor and four replications. The first factor was a type of trap (single funnel trap, multiple funnel trap, and mineral bottle) and the second factor was the height of trap (60; 120; 175; and 200 cm). The results showed that the type, height, and interactions were significant by coffee berry borer trapped. The best trap used by the mineral bottle with a height of 60 cm is 2.75 beetles. The type was of trap significant by the number of insects trapped and residue of attractant while height and interaction were nonsignificant. The best trap of insects trapped was a mineral bottle with height 175 cm is 21.8 individuals and the highest insect consisted of Formicidae amounted to 231 individuals with the residue of attractant is 0.73 ml.